1997
DOI: 10.1007/s002849900212
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Cold Shock Gene in Lactic Acid Bacteria and the Effect of Cold Shock on Cryotolerance

Abstract: When Lactic Acid Bacterial cultures were frozen at -20 degrees C for 24 h, the cell viability decreased drastically, but when they were cold shocked at 10 degrees C for 2 h prior to freezing, viability improved significantly for the Lactococcus lactis subsp. lactis strains (25-37%) and Pediococcus pentosaceus PO2 (18%), but not for the Lactococcus lactis subsp. cremoris strains tested or for one strain of Lactobacillus helveticus LB1 and Streptococcus thermophilus TS2. When the period for cold shock was extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 15 publications
3
36
0
Order By: Relevance
“…Since LAB starter cultures are frequently stored frozen, it is of practical relevance to monitor the abilities of these bacteria to survive freezing temperatures and to determine the critical factors for survival. L. lactis is able to adapt to freezing conditions by preexposure to 10°C, yielding increased survival in freezing conditions (20,35). For strain NZ9000, preexposure to 10°C for 2 and 4 h increased the survival of freezing approximately 50-and nearly 1,000-fold, respectively, after four repetitive freeze-thaw cycles (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Since LAB starter cultures are frequently stored frozen, it is of practical relevance to monitor the abilities of these bacteria to survive freezing temperatures and to determine the critical factors for survival. L. lactis is able to adapt to freezing conditions by preexposure to 10°C, yielding increased survival in freezing conditions (20,35). For strain NZ9000, preexposure to 10°C for 2 and 4 h increased the survival of freezing approximately 50-and nearly 1,000-fold, respectively, after four repetitive freeze-thaw cycles (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Indeed, LAB are generally naturally tolerant to freezing. Several studies demonstrated a correlation between CSP (CspL and CspP) produced after a cold-shock at suboptimal temperatures and cryotolerance (Kim and Dunn, 1997;Derzelle et al, 2003;Song et al, 2014).…”
Section: Technological Assessmentmentioning
confidence: 99%
“…The roles of these proteins are at the levels of membrane fluidity, DNA supercoiling and transcription and translation. Few papers have described cold shock proteins and mechanisms in LAB, in particular they have focused on Lactococcus lactis and L. plantarum [39][40][41][42]. Kim et al [39,40] tested different LAB to evaluate cold shock effects on cryotolerance.…”
Section: Principal Responses To the Most Common Stressesmentioning
confidence: 99%
“…Few papers have described cold shock proteins and mechanisms in LAB, in particular they have focused on Lactococcus lactis and L. plantarum [39][40][41][42]. Kim et al [39,40] tested different LAB to evaluate cold shock effects on cryotolerance. Improved understanding of cold-shock-induced cryotolerance may contribute to the development of environmental conditions that allow improved viability/activity of frozen or freeze-dried commercial LAB starter cultures.…”
Section: Principal Responses To the Most Common Stressesmentioning
confidence: 99%